2009
DOI: 10.1002/cncr.24191
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial wires releasing diffusing alpha emitters combined with chemotherapy improved local tumor control and survival in squamous cell carcinoma‐bearing mice

Abstract: BACKGROUND:The objective of this study was to examine the combined effect of diffusing alpha‐emitter radiation therapy (DART) together with the chemotherapeutic agent cisplatin on tumor development.METHODS:BALB/c mice bearing squamous cell carcinoma tumors were treated with radium 224 (224Ra‐)–loaded stainless steel wires, releasing short‐lived, alpha‐emitting atoms from their surface. A concomitant regimen of cisplatin doses (5 mg/kg per dose) was given intravenously for the evaluation of the combined effect.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 33 publications
(26 reference statements)
0
25
0
Order By: Relevance
“…Treatment with two 224 Ra-loaded wires and 5-FU had a pronounced retardation eff ect that further led to complete cure of 4 out of 5 mice. DaRT treatment could also be eff ectively combined with chemotherapy to treat squamous cell (Cooks et al 2009b) and pancreatic carcinoma (Horev-Drori et al 2012). Yet, exposure of tumor cells in vitro to chemotherapeutic drugs did not increase their sensitivity to alpha particles (unpublished results), so we assume that the increase in survival of the animals treated by the combination is due to eradication of lung metastases by the chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with two 224 Ra-loaded wires and 5-FU had a pronounced retardation eff ect that further led to complete cure of 4 out of 5 mice. DaRT treatment could also be eff ectively combined with chemotherapy to treat squamous cell (Cooks et al 2009b) and pancreatic carcinoma (Horev-Drori et al 2012). Yet, exposure of tumor cells in vitro to chemotherapeutic drugs did not increase their sensitivity to alpha particles (unpublished results), so we assume that the increase in survival of the animals treated by the combination is due to eradication of lung metastases by the chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, oncomiR‐370 is successful in triggering cell migration by disturbing the TGFβ signaling pathway . The tumor suppressor miR‐218 promotes invasion and metastasis via targeting Robo1, and thereby activating the Slit/Robo1 signaling pathway . Tang et al discovered that GSK3β suppressed the expression of miR‐183‐96‐182 clusters (miRNA‐96, miRNA‐182, and miRNA‐183) through the β‐Catenin/Tcf/Lef‐1 pathway .…”
Section: Role Of Mirnas In Signaling Pathways Of Gcmentioning
confidence: 99%
“…126 The tumor suppressor miR-218 promotes invasion and metastasis via targeting Robo1, and thereby activating the Slit/Robo1 signaling pathway. [127][128][129][130][131] Tang et al discovered that GSK3β suppressed the expression of miR-183-96-182 clusters (miRNA-96, miRNA-182, and miRNA-183) through the β-Catenin/Tcf/Lef-1 pathway. 132 It was found that miRNA-29s should have an effect on the Ras/Raf/MEK/ERK pathway, which acts on cell cycle progression by inducing of cell cycle regulatory proteins such as CDKs and cyclins.…”
Section: Role Of Mirnas In Signaling Pathways Of Gcmentioning
confidence: 99%
“…A second setup for in vitro irradiation by alpha particles relied on short exposures of cells, seeded on a 7.5-mm thick Kapton (polyamide) foil (Dupont, Luxembourg), to alpha particles emitted by a sealed 228 Th source (14). Cells were seeded on the Kapton foil at a density of 3 Â 10 5 cells/well and exposed to the alpha particle flux 24 h later.…”
Section: Kapton Wells Irradiation Setupmentioning
confidence: 99%
“…In previous articles (12)(13)(14), we described a new form of brachytherapy, which allows the treatment of solid tumors by alpha particles. The method, named diffusing alphaemitters radiation therapy (DART), relies on the utilization of implantable radioactive sources that carry small activities of radium-224 ( 224 Ra, 3.7 days half-life), incorporated into their surface.…”
Section: Introductionmentioning
confidence: 99%